2013
DOI: 10.1039/c3an00741c
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace amount of Cu2+ with a multi-responsive colorimetric and reversible chemosensor

Abstract: A multi-responsive sensor 1 was constructed by combining a ferrocene unit and a rhodamine block via a carbohydrazone bond. The sensor showed high selectivity toward Cu(2+) over other common metal ions in a wide pH range with excellent reversibility and rapid response. The obvious color change from colorless to pink upon the addition of Cu(2+) could make it a suitable 'naked-eye' indicator for Cu(2+). The detection limit (LOD) obtained was down to 2.0 nM and the association constant (Ka) was evaluated as 4.65 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…They exhibit a good linear relationship between the value of the photocurrent increase and the concentration of Cu 2+ . The linear response range is wider than those based on fluorescence quenching (1 to 10 μ M ),42 a fluorescence assay using fluorescence reagent (1.6 to 12 μ M ),43 or photoelectrochemical sensing (0.4 to 7.6 μ M 29 or 0.4 to 13 μ M 30). The detection limit was calculated to be 6.2 n M based on a signal‐to‐noise ratio ( S / N ) of 3.…”
Section: Resultsmentioning
confidence: 94%
“…They exhibit a good linear relationship between the value of the photocurrent increase and the concentration of Cu 2+ . The linear response range is wider than those based on fluorescence quenching (1 to 10 μ M ),42 a fluorescence assay using fluorescence reagent (1.6 to 12 μ M ),43 or photoelectrochemical sensing (0.4 to 7.6 μ M 29 or 0.4 to 13 μ M 30). The detection limit was calculated to be 6.2 n M based on a signal‐to‐noise ratio ( S / N ) of 3.…”
Section: Resultsmentioning
confidence: 94%
“…The detection limit of the sensor toward the copper ion was found to be as 2 μmol L −1 and the detection limit of the ligand-copper complex for the cyanide ion was calculated to be <1 μmol L −1 (0.06 ppm). Mi et al 205 reported a multi-responsive sensor 156 (Fig. 124) as a ratiometric and "off-on" chemosensor for Cu 2+ .…”
Section: Rhodamine Based Cu 2+ Sensormentioning
confidence: 99%
“…To this end, a number of sensors utilising uorescent dyes both in aqueous and organic phases has been reported. [11][12][13][14][15][16][17][18][19] Although high selectivity and sensitivity were achieved, such uorescent probes require meeting the challenge of multi-step synthesis and control of pH.…”
Section: Introductionmentioning
confidence: 99%